The Effect of Ladder Drill Training on the Dribbling Agility of Futsal Extracurricular Students - Misbahul, Misbahul; Widodo, Haryo Mukti; Hidayatullah, Fajar; Purwoto, Septyaningrum Putri (JSES : Journal of Sport and Exercise Science, 2024)
The main obstacle in mastering futsal playing techniques well is the player’s lack of agility when dribbling the ball. Agility is a physical component that is very important for sports that require speed in changing the direction of movement. In the sport of futsal, agility plays a crucial role in supporting a player’s performance to win the game. One of the agility exercises is the ladder drill exercise. This research is a type of pre-experimental research method (weak experiment). There are 2 variables in this study, with 1 independent variable (ladder drill training model) and 1 dependent variable, namely (agility). The design of this research is to use (pre-experimental designs). This research was conducted at SMP NU Arosbaya, located in Berbeluk Village, Arosbaya Bangkalan District. The population in this study was 10 students who participated in futsal extracurricular activities at SMP NU Arosbaya. The Wilcoxon test results showed a P value of 0.001 < 0.05, indicating a significant effect. Hence, ladder drill training significantly influences the dribbling ability of futsal extracurricular students. The advice in this research is that extracurricular futsal participants are expected to be able to perform good dribbling techniques in futsal games to make it easier to win every match.